Profile of type ii diabetes mellitus with central obesity in dr. Soetomo hospital - Munir, Misbakhul; Sutjahjo, Ari; Sustini, Florentina (Folia Medica Indonesiana, 2016)
Obesity, especially central obesity is often associated with insulin resistance and type 2 diabetes mellitus. Diabetes mellitus is a disease of the number six cause of death in Indonesia with the proportion of deaths by 5.8%. The purpose of this study was to identify central obesity in patients with type 2 diabetes mellitus in Poly Endocrine Dr. Soetomo Hospital, Surabaya. The study design was descriptive study. The sample was 100 type 2 diabetes mellitus patients taken with purposive sampling technique. The variable was central obesity and type 2 diabetes mellitus. The data obtained by interviewing patients and performing measurements on body weight, height and waist circumference. Data were analyzed by interpreting how the description of the variables studied and compared with other studies and theories. The results was the characteristics of patients most were female (66%), level of education was medium, unemployment, most of patient's age was more than 50 years old, 43% for interval 51-60 years old, 43% were 1,50-1,59 meters in height and 28% were 50-59 kilograms and 28% were 60-69 kilograms in weight. According to Body Mass Index (BMI) measure that 54% the patients are normal in average 25,56 8,12 kg/m2. Measurement of waist circumference showed that 73.5% male and 81.8% female patients had central obesity. The conclusions, precentage of patients with type II diabetes mellitus who have central obesity were 81,82% female and 73, 53% male.